The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.eurpsy.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of professionals’ attachment style, expectations and job attitudes for therapeutic relationships with young people who experience psychosis

Abstract: BackgroundTherapeutic relationships are a central component of community treatment for psychosis and thought to influence clinical and social outcomes, yet there is limited research regarding the potential influence of professional characteristics on positive therapeutic relationships in community care. It was hypothesised that professionals’ relating style and attitudes toward their work might be important, and thus this exploratory study modelled associations between these characteristics and therapeutic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Figure 1 summarises the progress of papers through different stages of the review. Thirteen papers [13][14][15][16][17][18][19][20][21][22][23][24][25] met criteria for inclusion, and were included in the final analysis ( Table 3 and 4). No randomised controlled trials or cohort studies were found.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…Figure 1 summarises the progress of papers through different stages of the review. Thirteen papers [13][14][15][16][17][18][19][20][21][22][23][24][25] met criteria for inclusion, and were included in the final analysis ( Table 3 and 4). No randomised controlled trials or cohort studies were found.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…To measure clinicians’ attitudes relating to working with people with distressing voices, a 35-item modified version ( McLeod et al, 2002 ) of the Alcohol and Alcohol Problems Perception Questionnaire (AAPPQ; Cartwright, 1980 ) was used. The original AAPPQ had been designed to capture therapists’ attitudes toward working with patients who abuse alcohol, and it has been modified ( McLeod et al, 2002 ; Berry and Greenwood, 2016 ) to capture attitudes of mental health professionals to working with people with psychosis. For the purpose of this study, the questionnaire items were amended to refer specifically to voice-hearing.…”
Section: Methodsmentioning
confidence: 99%